RESOURCES BOOKS OF NZHAH ALTRF IN MORPHOLOGY (Journal of the College of Education for Women, 2019)
This research aims to establish a morphological study of the sources wrote picnic party in Morphology The sources from which he took the owners wrote their material (Nzhah Altarf) morphological accurate survey requires full briefing survey.This is very difficult, because they were not mean with reference to the sources, who transferred them, so it was difficult to know the author, who mentioned it to say that on one hand, and on the other hand, find them do not deny preferred their predecessors of Arab scholars, and this is evidence of scientific integrity they have and high character they have, Sometimes we find that thay me htioh their opihios with their hames cite their views with anonymity, and sometimes their books and remember their names, and can be divided into the sources relied upon in all the information in their study to the morphological flags, books in chronological order according to their deaths.